A Study to Assess the Availability of Basic Facilities for Inmates in Geriatric Home, Ahmedabad, Gujarat, India - Banker, Kavita; Prajapati , Bipin; Kedia , Geeta (National Journal of Community Medicine, 2012)
Background: Ageing is a normal physiological process for human being, but modernization and globalization have disintegrated the Indian family system and elders are focused to stay in geriatric homes. The care for the aged is slowly shifting from the family to geriatric homes. Objective: To study the function of geriatric homes, background information and reasons for shifting to geriatric home. Material and Methods: A cross sectional study was carried out in geriatric homes of urban and periurban areas of Ahmedabad during January 2008 to January 2009. Result: All the geriatric homes were nongovernment organization. Out of total (13) geriatric homes, majority (76.9%) of them have the criteria for enrolment was the cut off age as 60 years or above. Out of total 530 inmates, 380(71.7%) inmates having children, out of them, maximum number of inmates had either two (28.9%) or three (23.9 %) children. According to education of inmates 29.6%were secondary and 25.5% were primary education. Among marital status of inmates, 78.8% were widow/widower. Familial conflict (53.6%) was major reason for shifting at geriatric home. Overcrowding was present in 38.5 % geriatric homes according to person per floor area. Majority of geriatric homes were having TV, library, garden, kitchen, availability of newspaper and adequate lighting, ventilation, water supply. Only 7.7% of geriatric homes had full time doctor while 61.5% had part time doctor. 84.6% of old age homes had paid staff of institute for sweeping and mopping and for cleaning utensils.